β-Catenin Regulation in Sporadic Colorectal Carcinogenesis: Not as Simple as APC - Ernst Fredericks; Gill Dealtry; Saartjie Roux (Canadian Journal of Gastroenterology and Hepatology)
Background. The wnt/APC/β-catenin pathway is a critical initiator in colorectal carcinogenesis in both hereditary and sporadic colorectal cancer (CRC). The progression of this process remains incompletely understood, although inflammation is pivotal. Drivers of inflammation are elevated in malignant tissue and have been shown to regulate β-catenin expression. Interleukin-17A (IL-17A) is protumorigenic at elevated levels via COX-2 stimulation. Elevated peroxisome proliferator-activated receptor γ (PPARγ) expression has reduced risk of carcinogenesis and good overall prognosis in established CRC. Activation of PPARγ has inhibitory effect on β-catenin. Methods. Using qPCR and IHC, we compared β-catenin, PPARγ, COX-2, and IL-17A in the colonic mucosa of patients with sporadic CRC, inflammatory bowel disease (IBD), and irritable bowel syndrome (IBS), against a normal control population. Results. β-catenin mRNA and protein expression progressively increased from the Normal group, through IBS and IBD reaching statistical significance in CRC. COX-2 mRNA levels increased similarly with statistical significance in IBD and CRC. However, COX-2 protein expression was inverted with significant expression in the Normal and IBS groups and reduced levels in IBD and CRC. PPARγ mRNA expression was unchanged in IBD and CRC but was significantly elevated in the IBS. IL-17A mRNA was significantly reduced in IBS and CRC but unchanged in IBD. There were no differences in all parameters tested in the Normal and IBS groups. Conclusion. β-catenin is confirmed as a major driver of colorectal carcinogenesis but is controlled by many more players other than APC. Elevated levels of PPARγ may have an anticarcinogenic effect. The role of COX-2 expression, especially its posttranscriptional regulation in colorectal cancer, needs further elucidation.